2010
DOI: 10.1111/j.1567-1364.2009.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomycesSUN gene,UTH1, is involved in cell wall biogenesis

Abstract: Deletion of the Saccharomyces gene, UTH1, a founding member of the SUN family of fungal genes, has pleiotropic effects. Several phenotypes of Δuth1 cells including their decreased levels of mitochondrial proteins, their impaired autophagic degradation of mitochondria, and their increased viability in the presence of mammalian BAX, a pro-apoptotic regulator localized to the mitochondria, have prompted others to propose that the Uth1p functions primarily at the mitochondria. In this report, we show that cells la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
4
28
3
Order By: Relevance
“…In the yeast S. cerevisiae , the four S. cerevisiae proteins act by remodeling the cell wall (Kuznetsov et al, 2013). In fact, knockout mutants in the UTH1 gene showed similar sensitivity to cell wall modifying substances (Kuznetsov et al, 2013) as reported here for Δ Bcsun1 mutants, and the reduction in the number of protoplasts generated from the UTH1 mutant strain has been related with an increase in β-1,6-glucan and chitin composition of the yeast cell wall (Ritch et al, 2010). SUN41 from C. albicans is also involved in morphogenesis, cell wall biogenesis and is necessary during yeast branching (Hiller et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the yeast S. cerevisiae , the four S. cerevisiae proteins act by remodeling the cell wall (Kuznetsov et al, 2013). In fact, knockout mutants in the UTH1 gene showed similar sensitivity to cell wall modifying substances (Kuznetsov et al, 2013) as reported here for Δ Bcsun1 mutants, and the reduction in the number of protoplasts generated from the UTH1 mutant strain has been related with an increase in β-1,6-glucan and chitin composition of the yeast cell wall (Ritch et al, 2010). SUN41 from C. albicans is also involved in morphogenesis, cell wall biogenesis and is necessary during yeast branching (Hiller et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…SIM1 plays an important role in the regulation of DNA replication (Dahmann et al, 1995), although when overproduced from a multicopy plasmid, SIM1 also functioned as an extracellular suppressor of mutations in the PAG1 and CBK1 genes involved in cellular morphogenesis (Du and Novick, 2002). UTH1 was first identified in a screening for S. cerevisiae mutants with increased stress resistance and longer life spans (Kennedy et al, 1995) and shows a dual localization: in mitochondria, where it is involved in mitochondrial biogenesis and autophagy (Camougrand et al, 2000) and in the cell wall, where it seems to play a role in determining the β-d-glucan/chitin composition (Ritch et al, 2010). The third member of the family, NCA3, is involved in the maturation of transcripts encoding two components of the ATP-synthase complex in mitochondria (Pelissier et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Uth1 has been proposed to act directly in both wall organization and autophagic destruction of mitochondria (Camougrand et al 2003Kissova et al 2004), but this is controversial (Kanki et al 2009). Recent evidence strongly suggests that Uth1 is primarily a cell wall hydrolase and many phenotypes seen when it is deleted are the result of strengthened cell walls (Ritch et al 2010).…”
Section: Septum Destructionmentioning
confidence: 99%
“…Importantly, all of the control strains analyzed, Sor5, m2, m5, m6, m7, m8, m15, and m16, retained a level of zymolyase resistance similar to that of the parental strain. Zymolyase resistance has been suggested to result from changes in the structure of the glucan network (38,39) or from masking, leading to less zymolase-mediated cleavage of 1,3-␤-glucan due to changes in the external mannoprotein layer (40,41). Ch5 copy number controls the level of 1,3-␤-glucan and chitin of the cell wall and the cellular level of ergosterol.…”
Section: Susceptibility To Antifungals In Candida Albicansmentioning
confidence: 99%